Impacts of the alloying elements and thermo-mechanical processing on the phase stability, crystalline structure, microstructure, and selected mechanical properties of Ti-(10-x)Al-xV (x = 0, 2, and 4 wt%) alloys targeted as external prostheses - Pinto, Bruna O. [UNESP]; Torrento, Jhuliene E.M. [UNESP]; Kuroda, Pedro A.B. [UNESP]; Correa, Mariana R. [UNESP]; Grandini, Carlos R. [UNESP]; Zambuzzi, William F. [UNESP]; Rau, Julietta V.; Fosca, Marco; Correa, Diego R.N. [UNESP] (Elsevier, 2024)
This study aimed to characterize Ti-Al-V alloys submitted to thermo-mechanical processes and evaluate their impact on the crystalline structure, microstructure, coefficient of thermal expansion (CTE), selected mechanical properties, and cytotoxicity. X-ray diffraction (XRD) analysis revealed a major α phase, with V acting as a β-stabilizer. The cooling rate and the plastic deformation contributed to the formation of minor martensitic α′ and β phases, with notable variations in cell parameters. The Energy-Dispersive XRD indicated the CTE was dependent on the alloying elements. Ti-10Al and Ti-8Al-2V depicted Widmanstätten laths and basket-weave structures, while Ti-6Al-4V showed typical features of β grain boundaries. Thermodynamic predictions aligned with the observed phase compositions. Vickers micro-hardness tests yielded values surpassing those of commercially pure titanium (CP-Ti), attributed to the synergistic effects of solid solution, phase precipitation, and strain hardening effects. And, elastic modulus approximated that of CP-Ti, largely due to the α phase's predominance. The solution treatment reduced the elastic modulus compared to the hot-rolled samples due to the stress relief and α′ and β phase precipitation. Preliminary cytotoxicity assays confirmed the non-toxicity of the samples to cell viability. These findings suggest that the solutionized Ti-10Al sample is an economically viable candidate for fabricating external prostheses.